1993
DOI: 10.2307/1591910
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy in Chickens of a Herpesvirus of Turkeys Recombinant Vaccine Containing the Fusion Gene of Newcastle Disease Virus: Onset of Protection and Effect of Maternal Antibodies

Abstract: The onset of protection against Newcastle disease and the effect of maternal antibodies to Newcastle disease virus (NDV) and Marek's disease virus (MDV) on vaccine efficacy were determined following vaccination of chickens with a recombinant herpesvirus of turkeys (HVT) vaccine expressing the fusion (F) glycoprotein gene of NDV. Onset of protection following intra-abdominal administration of the recombinant HVT/F vaccine at 1 day of age and subsequent ocular challenge with the neurotropic velogenic Texas GB st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…In the poultry industry, four recombinant viruses (rFPV [1,5,8,14,18,25,31,34,35,59], rHVT [13,17,28,41,44,53], adenovirus [51], and rMDV1 [45,47,49,54,62]) that express foreign antigens of other avian pathogens (including NDV [14, 17, 24, 28-30, 35, 47, 53, 58], MDV [31,33,42,44,69], infectious bursal disease virus [1,5,13,18,19,51,62], avian influenza virus [2,3,5,56,59,61,65,66], avian leukosis virus [34], and avian reticuloendotheliosis virus [8]) have been developed, and these viruses showed significant vaccine efficacy against a variety of avian diseases. Further, rHVT, rMDV1, and rFPV expressing NDV antigens have been constructed and used to FIG.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the poultry industry, four recombinant viruses (rFPV [1,5,8,14,18,25,31,34,35,59], rHVT [13,17,28,41,44,53], adenovirus [51], and rMDV1 [45,47,49,54,62]) that express foreign antigens of other avian pathogens (including NDV [14, 17, 24, 28-30, 35, 47, 53, 58], MDV [31,33,42,44,69], infectious bursal disease virus [1,5,13,18,19,51,62], avian influenza virus [2,3,5,56,59,61,65,66], avian leukosis virus [34], and avian reticuloendotheliosis virus [8]) have been developed, and these viruses showed significant vaccine efficacy against a variety of avian diseases. Further, rHVT, rMDV1, and rFPV expressing NDV antigens have been constructed and used to FIG.…”
Section: Discussionmentioning
confidence: 99%
“…rMDV1 showed almost 100% protective efficacy against NDV and MDV1 challenge in specific-pathogen-free (SPF) chickens lacking maternal antibodies from ND and MD by one-time inoculation, whereas the protective efficacy varied among experiments and decreased on average to 70% in chickens with maternal antibodies even though the challenge experiments were performed at a time when the maternal antibodies would not affect an evaluation of the protective efficacy. In the other systems using rHVT expressing NDV-F under the control of a strong promoter from the Rous sarcoma virus long terminal repeat and several recombinant fowl poxviruses (rFPV) expressing the NDV-F or hemagglutinin-neuraminidase gene, a similar problem with the maternal antibodies was also reported (14,25,28,29,35,57,58). Although it is not known why the recombinant polyvalent vaccines are not completely effective against the avian diseases in the presence of maternal antibodies, it is conceivable that the strong expression of these foreign genes induces a strong host immune reaction against the recombinant vaccines, which results in inhibition of the growth of the recombinant viruses in chickens.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…Some groups showed that HVT can be used as a viral vector for expression of antigen from other avian pathogens [20,73,74,98,103]. The recombinant HVT, expressing the fusion (F) antigen of Newcastle disease virus (NDV), protected chickens against challenge infection with virulent NDV and retained the capacity of HVT to protect against Marek's disease [73].…”
Section: ) Hvt Vectormentioning
confidence: 99%